The trustworthiness of travel and tourism information sources of social media: perspectives of international tourists visiting Ethiopia - Kassegn Berhanu; Sahil Raj (Heliyon, 2020)
Credibility of social media travel information sources is one of the most debatable topics among scholars. This research is designed to address the trustworthiness of travel and tourism information sources of social media platforms. Cross-sectional research design and convenience sampling was applied. Statistical Package for Social Science version 23 was employed to compute mean, one sample T-test, independent sample T-test and one-way Analysis of variance. Eta squared was calculated to measure the effect size or magnitude of mean difference. The effective sample size is 310 visitors. The findings revealed that visitors had a positive perception towards the trustworthiness of social media travel information sources. Visitors with the age of 18–35 years have a higher level of agreement towards the trustworthiness of social media travel information sources. As the age of visitors increases, the mean scores marginally decreases where the lowest mean scores lay on visitors who are above 46 years. Limitations and managerial/industrial implications are detailed.